Effects of Repeated Doses Administration of Methotrexate on Rat Liver Tissue - Kocaman, Nevin; Çolakoğlu, Neriman (Fırat University, 2013)
Objective: Methotrexate is a commonly prescribed drug to therapy many of disorders including cancer, rheumatoid arthritis, psoriasis thanks to anti cancer, anti inflammatory properties. Nevertheless, its use is associated with the risk of hepatotoxicity due to metabolized in liver. This experimental study was planned to determined possible hepatic injury caused by methotrexate. Material and Method: Total of 18 adult Wistar Albino female rats were used. The animals were diveded into 3 groups. The rats in the 1st group were used as control. The second group of rat were injected single dose methotrexate (15mg/kg) on 1st day of experimental study, whereas third group of rats were injected methotrexate 1st and 5th day of experimental study. All of rats were decapitated on 8th day of experiment. Midsaggital incision was performed and liver tissues were removed and fixed in 10% formaldehyde solution for light microscopy investigations. Results: In light microscopic examination, there were vascular congestion, sinusoidal dilatation, mononuclear cell infiltration in periportal space in group II. In addition, limited number hepatocytes had heterochromatin nuclei. In group III, vascular congestion and sinusoidal dilatation were observed more expansive. The other microscopic evidences were periportal inflammation and macrovesicular steatosis. Moreover, fibroblast activation was detected prominently. Conclusion: As a result of this study, physicians must be careful about adjustment of methotrexate, used to in the treatment of many diseases, dose and therapy time. Long-term prepared treatment protocols may impact on liver adversely as structural and physiological.

Amaç: Metotreksat, antikanserojen, antiinflamatuar özellikleri sayesinde kanser, romatoid artrit, psoriazis gibi çok sayıda hastalığın tedavisinde yaygın bir şekilde reçete edilmektedir. Bununla birlikte karaciğerde metebolize olmasından dolayı hepatotoksisite riski bulunmaktadır. Bu çalışma metotreksat kaynaklı muhtemel karaciğer hasarını belirlemek için planlandı. Gereç ve Yöntem: Çalışmada 18 adet Wistar Albino cinsi dişi sıçan kullanıldı. Denekler 3 gruba ayrıldı. Grup I'deki sıçanlar kontrol olarak kullanıldı. Grup II'yi oluşturan sıçanlara deneyin 1.gününde tek doz 15mg/kg metotreksat intra peritoneal (ip) yolla, grup III'teki sıçanlara ise deneyin 1. ve 5. günlerinde metotreksat i.p. yolla uygulandı. Deneyin 8. gününde tüm gruplarda yer alan sıçanlar dekapite edildi. Midsaggital insizyon yapılıp karaciğer dokuları ışık mikroskobik incelemeler için %10'luk formaldehit solüsyonuna alındı. Bulgular: Yapılan ışık mikroskobik incelemelerde grup II'de vasküler konjesyon, sinüzoidal dilatasyon, periportal alanda mononükleer hücre infiltrasyonu ve az sayıda heterokromatik çekirdekli hepatositler dikkat çekiciydi. Grup III'te ise vasküler konjesyonun ve sinüzoidal dilatasyonun oldukça yaygın olduğu saptandı. Periportal inflamasyon, makroveziküler yağlanma ve çok sayıda heterokromatik çekirdekli hepatosit ayırt edilen diğer bulgulardı. Ayrıca bu grupta belirgin fibroblast aktivasyonu saptandı. Sonuç: Bu çalışmanın sonucunda kliniklerde birçok hastalığın tedavisinde kullanılan metotreksatın doz ve süre ayarlamasının oldukça dikkatli yapılması gerektiği sonucuna varıldı. Uzun süreli hazırlanan tedavi protokolleri karaciğeri yapısal anlamda dolayısıyla fizyolojik olarak menfi yönde etkiliyebilir.
Tekrarlayan Dozlarda Metotreksat Uygulamasının Sıçan Karaciğer Dokusu Üzerine Etkileri